Role of Supervising teachers in the implementation Teaching Improvement at MAN 1 Padangsidimpuan - Saiful Akhyar Lubis, Nurkhoiriyah Siregar (International Journal Of Education, Social Studies, And Management (IJESSM), 2021)
This study aims to reveal: 1) The activities carried out by the supervising teacher in carrying out the diagnosis of student learning difficulties as preparation for implementation in teaching improvement at MAN 1 Padangsidimpuan, 2) Activities carried out by the supervisor in providing repair assistance ( remedial teaching) in MAN 1 Padangsidimpuan, and 3) Activities carried out by the supervising teacher in the assessment and follow-up of the implementation of teaching improvements at MAN 1 Padangsidimpuan. This research uses a qualitative approach, phenomenological research type, and descriptive analysis method. Data collection techniques are carried out by; participatory observation, in-depth interviews, and document analysis. The data analysis process was carried out starting from; data reduction, data presentation, and conclusions. Test the validity of the Data with credibility, transferability, dependability, and confirmability. The results of this study are: 1) Diagnosis of student learning difficulties in preparation for improvement teaching activities is carried out through four stages, namely identification of students, identification of locations and types of learning difficulties, determining factors causing learning difficulties and planning assistance, 2) Implementation of teaching improvement is carried out by counseling teachers. through the implementation of assistance, where this activity is directed at giving assignments, providing learning services related to learning methods and habits, learning motivation and interest in learning services, and 3) The efforts made by the supervisors in the implementation of teaching improvements, especially concerning assessment and follow-up are carried out continuously together through coordination and discussion between BK teachers and subject teachers.